2002
DOI: 10.1088/0957-4484/13/3/337
|View full text |Cite
|
Sign up to set email alerts
|

Giant optical transmission of sub-wavelength apertures: physics and applications

Abstract: The transmission of light through an aperture in a metal film is extremely small when the aperture diameter is much smaller than the optical wavelength. But when the metal surface surrounding the subwavelength hole is corrugated, the incident light can couple to surface plasmons (SP), excitation modes on the metal surface. A resonant interaction leads to an enhanced transmission at wavelengths determined by the corrugation pitch. We discuss applications of the SP enhanced transmission in near-field scanning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 24 publications
1
104
0
Order By: Relevance
“…[26,27,28] This once again emphasizes the difference between the properties of the near-field and the far-field and underlines the importance of performing near-field experiments.…”
Section: Introductionmentioning
confidence: 78%
“…[26,27,28] This once again emphasizes the difference between the properties of the near-field and the far-field and underlines the importance of performing near-field experiments.…”
Section: Introductionmentioning
confidence: 78%
“…In particular, periodic structures around a nano-aperture are of great interest because the optical transmittance through these systems can be largely tailored with respect to that of an isolated aperture. Bull's eye (BE) structures, consisting of a subwavelength aperture surrounded by annular grooves, have revealed that the transmitted light through the aperture can be strongly boosted and concentrated due to the excitation of surface plasmons (SP) launched by the periodic corrugations [4][5][6][7][8][9][10][11][12][13]. Attention has recently been given on coherent optical properties that are at play on BE structures where the direct transmission of light through the aperture interferes with an SP component launched by the corrugations.…”
Section: Introductionmentioning
confidence: 99%
“…However, by using periodic grooves around the aperture on the input surface, transmission efficiency could be greatly enhanced (see e.g. [3][4][5][6]). Such a phenomenon has been intensively studied [7][8][9] and can be applied in many potential applications [10,11].…”
mentioning
confidence: 99%